Mobile Applications in Cell Biology Present New Approaches for Cell Modelling. Issue 3 (2nd July 2016) - de Oliveira, Mayara Lustosa; Galembeck, Eduardo
Abstract : Cell biology apps were surveyed in order to identify whether there are new approaches for modelling cells allowed by the new technologies implemented in tablets and smartphones. A total of 97 apps were identified in 3 stores surveyed (Apple, Google Play and Amazon), they are presented as: education 48.4%, games 26.8% and medicine 15.4%. The apps were arranged by representation similarities of the cell models, and then the groups were nominated. The name of each one was based in recurrent terms on the apps descriptions and the definition is grounded in the literature. Thus, we categorized those apps in six modelling groups, not mutually exclusive: 32% three-dimensional, 25% bi-dimensional, 14% realistic, 14% animation, 11% scale and 4% playful. Each model has unique characteristics. Three-dimensional models can present proportional scales of organelles that allow immersion in the cell model. Realistic models and animations can be used to explore the dynamics of the cell functioning. The cell models designed for smartphones and tablets bring handling capabilities not found in computers and notebooks; they also have the potential to deliver content with high levels of interactivity and are accessible anytime and anywhere. Regarding the applicability of the cell models available in the apps, this paper offers some suggestions of classroom use based on the features of the models and examples found in the literature.